Structural Characterization and Discrimination of Morinda officinalis and Processing Morinda officinalis Based on Metabolite Profiling Analysis - Kang, Liping; Zhang, Yan; Zhou, Li; Yang, Jian; He, Yali; Yang, Shuai; Li, Gai; Hao, Qingxiu; Yu, Yi; Guo, Lanping (Frontiers in Chemistry, 2022)
Morindae officinalis Radix (MOR) is a famous traditional Chinese medicine (TCM) and functional food material for invigorating kidneys and strengthening yang. Processing Morinda officinalis Radix (PMOR) is obtained by steaming MOR. MOR and PMOR are commonly used both clinical practice and dietary supplements. To clarify the overall chemical composition and the difference of MOR and PMOR, a method was developed with an ultrahigh-performance liquid chromatography coupled with quadrupole time-of-flight mass spectrometry (UHPLC-Q-TOF/MS). Among the 110 identified components shared by MOR and PMOR, 57 compounds showed significant differences in contents. Among them, the contents of 31 components, including fructooligosaccharides, monotropein, deacetylasperulosidic acid, geniposide, and anthraquinone glycosides, were higher in MOR than in PMOR; the contents of 26 components, including difructose anhydrides sucrose and iridoid glycoside derivatives, were higher in PMOR than in MOR. Difructose anhydrides and iridoid glycoside derivatives were first discovered in PMOR. These results provided a scientific basis for research on the therapeutic material basis of MOR. It would provide a method for the comparison of processing and non-processing Chinese medicines